2007
DOI: 10.1097/mpg.0b013e31802c0ceb
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Small Bowel Bacterial Overgrowth in Cystic Fibrosis

Abstract: Patients with CF were more likely to have elevated fasting hydrogen levels compared with controls. This suggests a high prevalence of small bowel bacterial overgrowth in CF patients. Medications commonly used by CF patients may influence intestinal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 42 publications
4
81
1
3
Order By: Relevance
“…However, BIO also seems to be involved in other intestinal disorders, e.g., the irritable bowel syndrome [6,13,14]. Though an increased prevalence of BIO has already been described, even in children with cystic fibrosis (CF), further clinical studies confirming these findings are scarce [15,16]. Recently, Norkina et al [17] reported on the inflammatory effects of bacterial intestinal overgrowth in the cystic fibrosis mouse small intestine.…”
Section: Introductionmentioning
confidence: 93%
“…However, BIO also seems to be involved in other intestinal disorders, e.g., the irritable bowel syndrome [6,13,14]. Though an increased prevalence of BIO has already been described, even in children with cystic fibrosis (CF), further clinical studies confirming these findings are scarce [15,16]. Recently, Norkina et al [17] reported on the inflammatory effects of bacterial intestinal overgrowth in the cystic fibrosis mouse small intestine.…”
Section: Introductionmentioning
confidence: 93%
“…Hydrogen and methane cannot be produced by host-cell metabolism but are the products of microbial fermentation; the magnitude of the gas levels is proportional to the concentration of bacteria. Using breath testing, SIBO has been found in about one-half of CF patients (Lewindon et al 1998;Fridge et al 2007;Lisowska et al 2009Lisowska et al , 2010. Also using breath testing, several studies have reported that orocecal transit is frequently slower in CF (Bali et al 1983;Escobar et al 1992;Murphy et al 1992;Lewindon et al 1998).…”
Section: Microbial Dysbiosismentioning
confidence: 99%
“…Laxativetreated CF mice apparently have less mucus accumulation and less dilation of the intestinal crypt lumen compared with liquid-fed mice (9), although this previously has not been quantitatively compared. PEG-based laxative is also used clinically to treat intestinal obstruction in CF patients (11), and its use is associated with a significant decrease in the occurrence of SIBO (18).…”
mentioning
confidence: 99%